Reproductive Toxicity Analysis of Potential Toxic Element Lead in Mice and their Regenerative Potential - Kumar, Vaneet; Bhatti, Sandip Singh; Sharma, Sushma; Nagpal, Avinash Kaur (Asian Journal of Biological and Life Sciences)
World Health Organization has highlighted the increase in rates of infertility and poor reproductive health globally and potential toxic elements are among the major culprits for increase in infertility. The present study was conducted to evaluate the hypothesis that “the germ cells of mice have regenerative potential to recover from toxicity induced because of heavy metal exposure”. For this, experiments were conducted to analyze in vivo reproductive toxicity of lead acetate in male mice (Mus musculus) and the self-regenerative potential of their germ cells. A total of 27 male mice (Mus musculus) were grouped into 3 groups containing 9 animals each. Group 1 animals were given oral treatment of lead acetate (10 mg/kg b.w.) on daily basis; while Group 2 animals were administered 50 mg/kg b.w. on weekly basis; and Control group were administered distilled water. Three animals from each group were selected randomly after 24 hr and 40 days of treatment. The remaining animals were given normal diet for next 40 days to check the regenerative potential of animal’s germ cells. Animals from each group after 24 hr, 40 and 80 days were sacrificed by cervical dislocation and sperm abnormality assay was performed. The results revealed that lead acetate induced significantly higher sperm abnormalities in mice than the control group. The study also indicated that mice can show significant self-regenerative potential of germ cells after period of recovery.
Keywords: Lead acetate; Mus musculus; Potential toxic elements; Reproductive health; Sperm abnormality assay